ANALISIS RELIABILITY CENTERED MAINTENANCE (RCM) PADA ALAT BONGKAR MUAT RUBBER TYRE GANTRY CRANE (RTGC) DI PT XXX - Rahmatulloh; Suharto; Riana Septiani (Fakultas Teknik Universitas Tulang Bawang Lampung, 2021)
The loading and Unloading operational activities in port often run into obstacle, because happened malfunction occurrence of the equipment used. Failure to operate the equipment has resulted in downtime decreased of company productivity. Therefore, a system is needed maintenance of planning in order to produce the equipment that can be operated optimally. This research was choosen the company PT. XXX which is a company that enganged in the field maintenance of equipments port operational (quayside container crane, rubber tyre gantry crane, gantry luffing crane, and others) the place where the equipment maintenance system, especially the rubber tyre gantry crane (RTGC) which has been done are still a breakdown maintenance and corrective maintenance. The aim of this research is to analyze by method of reliability centered maintenance (RCM) to able to determined the optimal maintenance and it can be predict steps to overcome the damage that might will happen in the next period based on existing data. From data processing and analysis was obtained that the components most frequently damaged on the equipment of RTGC, cause of failure, selection decision and recommendations for maintenance systems are based on Reliability Centered Maintenance (RCM).